RELIGIOUS RHETORIC AND REFORM: A CASE STUDY OF INDIA - Gautam, Kumar Jha (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2017)
Nationalist movements in India during the mid 19th century took momentum and gained popularity when various intellectual freedom fighters started reinterpreting the religious texts motivating the educated people. The reinterpretation was oriented towards inducing the mass with the feeling of self-consciousness and nationalism. Most of these freedom fighters i.e. Bankimchandra Chatterjee, Bal Gangadhar Tilak, Swami Vivekanada, Aurobindo Ghose, Mahatma Gandhi, Vinoba Bhave, who wrote extensively on âBhagavad Gitaâ and their basic interpretation converged on ethical and moral basis for nationalism. Nationalist leaders like Bal Gangdhar Tilak who wrote Gita Rahasya in which he has justified the use of violence for the cause of nation unlike Mahatma Gandhi and Vonobha Bhave who oriented interpretation of Gita towards non-violence. However, both the interpretations worked in mobilizing the people against the imperialism by invoking conscience of the mass towards nationalism through religious texts. The article will deal with the stepwise process of highlighting religious texts and their reinterpretation by the leaders towards nationalism.